Searching for GEMS: TOI-5688 A b, a Low-density Giant Orbiting a High-metallicity Early M-dwarf - Varghese Reji; Shubham Kanodia; Joe P. Ninan; Caleb I. Cañas; Jessica Libby-Roberts; Andrea S. J. Lin; Arvind F. Gupta; Tera N. Swaby; Alexander Larsen; Henry A. Kobulnicky; Philip I. Choi; Nez Evans; et al. (The Astronomical Journal, 2025)
We present the discovery of a low-density planet orbiting the high-metallicity early M-dwarf TOI-5688 A b. This planet was characterized as part of the search for transiting giant planets ( R  ≳ 8 R _⊕ ) through the Searching for Giant Exoplanets around M-dwarf Stars (GEMS) survey. The planet was discovered with the Transiting Exoplanet Survey Satellite, and characterized with ground-based transits from Red Buttes Observatory, the Table Mountain Observatory of Pomona College, and radial velocity (RV) measurements with the Habitable-Zone Planet Finder on the 10 m Hobby Eberly Telescope and NEID on the WIYN 3.5 m telescope. From the joint fit of transit and RV data, we measure a planetary mass and radius of 124 ± 24 M _⊕ (0.39 ± 0.07 M _J ) and 10.4 ± 0.7 R _⊕ (0.92 ± 0.06 R _J ), respectively. The spectroscopic and photometric analysis of the host star TOI-5688 A shows that it is a metal-rich ([Fe/H] = 0.47 ± 0.16 dex) M2V star, favoring the core-accretion formation pathway as the likely formation scenario for this planet. Additionally, Gaia astrometry suggests the presence of a wide-separation binary companion, TOI-5688 B, which has a projected separation of ~5″ (1110 au) and is an M4V, making TOI-5688 A b part of the growing number of GEMS in wide-separation binary systems.